Efficacy and safety of macitentan in Fontan-palliated patients: 52-week randomized, placebo-controlled RUBATO Phase 3 trial and open-label extension - Clift, Paul; Berger, Felix; Sondergaard, Lars; Antonova, Petra; Disney, Patrick; Nicolarsen, Jeremy; Thambo, Jean-Benoît; Tomkiewicz Pajak, Lidia; Wang, Jou-Kou; Schophuus Jensen, Annette; Efficace, Michela; Friberg, Michael; et al. (The Journal of thoracic and cardiovascular surgery, 2025)
OBJECTIVES: The efficacy and safety of macitentan, an endothelin receptor antagonist, were assessed in a 52-week, prospective, multicenter, double-blind, randomized, placebo-controlled, parallel-group study assessing the efficacy and safety of macitentan in Fontan-palliated adult and adolescent patients (RUBATO-DB) and an open-label extension trial (RUBATO-OL). METHODS: Patients aged 12 years and older with New York Heart Association functional class II or III underwent total cavopulmonary connection more than 1 year before screening and showed no signs of Fontan failure/clinical deterioration. In RUBATO-DB, the primary efficacy end point was change in peak oxygen consumption from baseline to week 16; secondary end points were change from baseline over 52 weeks in peak oxygen consumption and change in mean count/minute of daily physical activity via accelerometer from baseline to week 16. Safety was assessed throughout both studies. RESULTS: In RUBATO-DB, 137 patients were randomized to macitentan 10 mg (n = 68) or placebo (n = 69); 92.7% completed 52-week double-blind treatment. At week 16, mean ± SD change in peak oxygen consumption was -0.16 ± 2.86 versus -0.67 ± 2.66 mL/kg/minute with macitentan versus placebo (median unbiased treatment difference estimate, 0.62 mL/kg/minute [99% repeated CI, -0.62 to 1.85]; P = .19). No treatment effect was observed in either of the secondary end points. During RUBATO-DB, most common adverse events with macitentan were headache, nasopharyngitis, and pyrexia. Across RUBATO-DB and RUBATO-OL, most common adverse events were COVID-19, headache, and fatigue. RUBATO-OL was prematurely discontinued because RUBATO-DB did not meet its primary or secondary end point. CONCLUSIONS: The primary end point of RUBATO-DB was not met; macitentan did not improve exercise capacity versus placebo in patients with Fontan palliation. Macitentan was generally well tolerated over long-term treatment.
Keywords: antagonisté endotelinového receptoru A; exercise test; Fontan Procedure; lidé; mladiství; výsledek terapie; Adult; antagonisté endotelinového receptoru; sulfonamidy; prospektivní studie; Fontanova operace; congenital; Endothelin Receptor Antagonists; Female; dítě; heart defects; Adolescent; Humans; pyrimidiny; Prospective Studies; Double-Blind Method; Endothelin A Receptor Antagonists; mužské pohlaví; vrozené srdeční vady; mladý dospělý; Sulfonamides; Time Factors; ženské pohlaví; Young Adult; endothelin receptor antagonist; open label; Treatment Outcome; spotřeba kyslíku; časové faktory; Male; Child; dvojitá slepá metoda; dospělí; Pyrimidines; Heart Defects, Congenital; Oxygen Consumption; Fontan procedure